Continent-wide parallel urban evolution of increased heat tolerance in a common moth - Merckx, Thomas; Nielsen, Matthew E; Kankaanpää, Tuomas; Kadlec, Tomáš; Yazdanian, Mahtab; Kivelä, Sami M (Evolutionary applications, 2024)
Urbanization and its urban-heat-island effect (UHI) have expanding footprints worldwide. The UHI means that urban habitats experience a higher mean and more frequent extreme high temperatures than rural habitats, impacting the ontogeny and resilience of urban biodiversity. However, many organisms occupy different microhabitats during different life stages and thus may experience the UHI differently across their development. While evolutionary changes in heat tolerance in line with the UHI have been demonstrated, it is unknown whether such evolutionary responses can vary across development. Here, using common-garden-reared Chiasmia clathrata moths from urban and rural populations from three European countries, we tested for urban evolution of heat shock tolerance in two life stages: larvae and adults. Our results indicate widespread urban evolution of increased heat tolerance in the adult stage only, suggesting that the UHI may be a stronger selective agent in adults. We also found that the difference in heat tolerance between urban and rural populations was similar to the difference between Mid- and North-European regions, suggesting similarity between adaptation to the UHI and natural, latitudinal temperature variation. Our observations incentivize further research to quantify the impact of these UHI adaptations on fitness during urbanization and climate change, and to check whether life-stage-specific adaptations in heat tolerance are typical of other ectothermic species that manage to survive in urbanized settings.
Keywords: urban‐heat‐island effect (UHI); lepidoptera; urban evolution; heat knock‐down time (HKDT); heat tolerance; latitudinal variation